2021
DOI: 10.2965/jwet.20-114
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Changes of Water Quality Parameters Pattern in Anzali International Wetland Using Remote Sensing

Abstract: In this study, the environmental monitoring of Anzali international wetland (based on water surface temperature (WST), chlorophyll-a (Chl-a) and transparency (secchi disk depth (SDD)) parameters) using Landsat images in the period 1985-2018 has been studied. Based on the results of zoning maps, in 2018 and 2013, WST fluctuations are higher, with the lowest water temperature observed in 2007.Based on Chl-a, the trend for this parameter is increasing from 1985 to 2018. Also, from 1985 to 2018, we saw a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The reports indicate the accuracy of measurements varies from case to case, and it depends on many factors (i.e.). But in general, high accuracy has been reported for measuring suspended solids (Pirali Zefrehei et al, 2021), turbidity (Weiqi et al, 2008), total nitrogen and phosphour (Sun, 2014), pH (Pereira et al, 2020), total dissolved solids (Aljoborey and Abdulhay, 2019), chloride (Amirsalari et al 2013), organic matter (Li et al, 2018), chlorophyII (Palmer et al, 2015) and dissolved oxygen (El Din et al, 2017). Weiqi et al, (2008) measured the values of turbidity, total nitrogen, ammonium, nitrate, total phosphorus and soluble phosphorus in Guanting Reservoir, Beijing, using Landsat 5 TM satellite images.…”
Section: Introductionmentioning
confidence: 99%
“…The reports indicate the accuracy of measurements varies from case to case, and it depends on many factors (i.e.). But in general, high accuracy has been reported for measuring suspended solids (Pirali Zefrehei et al, 2021), turbidity (Weiqi et al, 2008), total nitrogen and phosphour (Sun, 2014), pH (Pereira et al, 2020), total dissolved solids (Aljoborey and Abdulhay, 2019), chloride (Amirsalari et al 2013), organic matter (Li et al, 2018), chlorophyII (Palmer et al, 2015) and dissolved oxygen (El Din et al, 2017). Weiqi et al, (2008) measured the values of turbidity, total nitrogen, ammonium, nitrate, total phosphorus and soluble phosphorus in Guanting Reservoir, Beijing, using Landsat 5 TM satellite images.…”
Section: Introductionmentioning
confidence: 99%
“…Pirali Zefrehei et al showed the decrease in transparency of Anzali wetland from 1985 to 2018. This indicates an increase in the concentration of suspended and organic particles in the wetland, which leads to a decrease in water quality in water bodies [21,22]. Anzali wetland provides spawning and nursery grounds for commercial species of the Caspian Sea [17].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%